Social Communication and its Development in the Knowledge Society in Times of the Digital Age (London Journal of Research In Humanities and Social Sciences, 2023)
To speak of social communication means to refer to man himself. Its origin is as old as the human being. Hence, communication is based on signs and sounds. However, language is its main characteristic. An element that has evolved throughout the history of the individual. Therefore, in the twentieth century, social communication takes on academic importance, after establishing itself as a discipline and emerging as a science. Not in vain the evolution of technology has made the communication channels used a few decades ago, are almost obsolete compared to broadband communication that allows to establish contact in real time with good image and sound quality. In the society of knowledge and technology, the development of society is closely linked to social communication, if we take into account that it is of utmost importance for human growth. Although the digital age facilitates communication between humans, it brings as a consequence a challenge of equal magnitude: although mobile devices wereinvented so that man could communicate with other individuals, this has caused a large part of humanity to lose the tradition of talking to other peop
Keywords: communication; receptor emitter; technology &language